1996
DOI: 10.1007/bf00051131
|View full text |Cite
|
Sign up to set email alerts
|

Pranidipine, a novel calcium antagonist, once daily, for the treatment of hypertension: A multicenter, double-blind, placebo-controlled dose-finding study

Abstract: The antihypertensive effects and tolerance of once-daily (od), pranidipine, a novel dihydropyridine derivative with a long duration of action, were evaluated in a double-blind, placebo-controlled, parallel-group dose-finding study. A total of 199 patients, with a diastolic blood pressure (BP) of 95-115 mmHg, were included in the trial. After 4 weeks on placebo, patients were randomly assigned to either placebo or pranidipine at 1, 2, 4, or 8 mg od for a further 4 weeks. A dose response was seen in the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The dose of amlodipine they used was 20-100 times greater than that of pranidipine. Several other studies have demonstrated that amlodipine (2.5-10 mg/day) and pranidipine (1-4 mg/day) provided a consistent antihypertensive effect in a larger proportion of patients with hypertension [28][29][30] . Previously, we reported that pranidipine (0.3 mg/kg) improved cardiac function in rats with heart failure [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The dose of amlodipine they used was 20-100 times greater than that of pranidipine. Several other studies have demonstrated that amlodipine (2.5-10 mg/day) and pranidipine (1-4 mg/day) provided a consistent antihypertensive effect in a larger proportion of patients with hypertension [28][29][30] . Previously, we reported that pranidipine (0.3 mg/kg) improved cardiac function in rats with heart failure [14] .…”
Section: Discussionmentioning
confidence: 99%
“…This type of calcium channel antagonist appears to have fewer negative inotropic effects than earlier short-acting calcium channel antagonists [11][12][13]. Pranidipine is a similar type of long-acting calcium channel antagonist, which also has other pharmacological properties such as venodilator effects [14][15][16]. However, it is still unclear whether pranidipine prevents ventricular remodeling and progressive cardiac dysfunction in ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%